Threads of place: understanding the intangible memories of space and place – the case of Stellenbosch - Davids, Sahlah (School of Architecture, Planning and Geomatics, 2023)
Stellenbosch Town situated north of Cape Town holds remnants of the aftermath of the apartheid Regime. The reality of dispossession in the context of Die Vlakte, the fractured connection of Kayamandi to the Stellenbosch core, and other neighbourhoods that lie along the peripheries of the privileged and well-resourced centre, are all encompassed in the context of Stellenbosch. The less tangible history of Die Vlakte, a multi- racial community that was declared a white-only area due to the Group Areas Act of 1950. At the start of democracy, those dispossessed had the opportunity to claim land that was lost during the forced removals (Du Toit, 2010). Despite this, there is a continued spatial disjunction and fraction that echoes that of apartheid spatial planning. The sense of place evident in the Stellenbosch historical core currently lacks representation of individuals and communities of Die Vlakte and Kayamandi. Despite the tangible evidence of place concerning the built fabric; a sense of place is held further in the intangible memories, meanings, and narratives of individuals. This document explores elements of the intangible that is to make space and place, a sociopolitical art practice that is grounded in spatial form, historical influences that take place, and analysis of the street within Stellenbosch. In discovering what these aspects are, this research aims at uncovering potential approaches to design spaces for reconciliation that are empathetic to past and current injustices.